EFEKTIFITAS PENGUSIR NYAMUK ELEKTRIK DARI EKSTRAK KULIT DURIAN (DuriozibethinusMurr) - Mardiyah, Siti (Universitas Muhammadiyah Surabaya)
EFEKTIFITAS PENGUSIR NYAMUK ELEKTRIK DARI EKSTRAK KULIT DURIAN (DuriozibethinusMurr) Â By. Siti Mardiyah, Moh.Imam RoyaldiÂ Prodi D3 Analis UM SurabayaÂ ABSTRACTAedesaegypti is a type of mosquito that can carry dengue virus causes dengue fever. Efforts to eradicate the Aedesaegypti mosquito as a vector of dengue fever have often done, but the lack of public awareness about environmental hygiene still hamper such efforts. Therefore, the electric mosquito repellent products, which are considered practical to avoid mosquito bites, are widely used. However, the use of such products has the potential to cause environmental pollution and health problems. Durian rind extract is a natural insecticide materials that could become an alternative material as a substitute chemicals of mosquito repellent products.This research is an experimental study that aims to compare the repelling power effectiveness between durian rind extract and electric mosquito repellent in repelling Aedesaegypti mosquito. The population in this study is the Aedesaegypti mosquito breeding obtained from from East Java Provincial Health Office with samples taken as 640 mosquitoes were put in each room with 15 tails.The results showed that there are differences in effectiveness of repelling power between the durian rind extract and electric mosquito repellent in repelling the Aedesaegypti mosquito. This was evidenced by statistical tests using independent t test in which the value Tcount = 12.603 with sign value. 0.000 <0.005, which means H0 is rejected or no difference. The big difference is because the active substance in extracts of different anti-mosquito durian and it also shows that the durian rind extract has expelled under the power of an electric mosquito repellent. So, to have equal power of repelling with the electric mosquito, it needs durian rind extract concentration which is greater than 25%.Keywords: Aedesaegypti, durian rind extract DuriozibethinusMurr